An impact of superior vena cava isolation in non‐paroxysmal atrial fibrillation patients with low voltage areas. Issue 4 (18th May 2021) - Omuro, Takuya; Yoshiga, Yasuhiro; Ueyama, Takeshi; Shimizu, Akihiko; Ono, Makoto; Fukuda, Masakazu; Kato, Takayoshi; Ishiguchi, Hironori; Fujii, Shohei; Hisaoka, Masahiro; Kobayashi, Shigeki; Yano, Masafumi
Abstract: Background: This study aimed to investigate the correlation between left atrial low‐voltage areas (LVAs) and an arrhythmogenic superior vena cava (SVC) and the impact on the efficacy of an empiric SVC isolation (SVCI) along with a pulmonary vein isolation (PVI) of non‐paroxysmal atrial fibrillation (non‐PAF) with or without LVAs. Methods: We retrospectively enrolled 153 consecutive patients with non‐PAF who underwent a PVI alone (n = 51) or empiric PVI plus an SVCI (n = 102). Left atrial voltage maps were constructed during sinus rhythm to identify the LVAs (<0.5 mV). An arrhythmogenic SVC was defined as firing from the SVC and an SVC associated with the maintenance of AF‐like rapid SVC activity. Results: An arrhythmogenic SVC and LVAs were identified in 28% and 65% of patients with a PVI alone and 36% and 73% of patients with a PVI plus SVCI, respectively ( P = .275 and P = .353). In the multivariate analysis a female gender, higher pulmonary artery systolic pressure (PAPs), and arrhythmogenic SVC were associated with the presence of LVAs. In the PVI plus SVCI strategy, there was no significant difference in the atrial tachyarrhythmia/AF‐free survival between the patients with and without LVAs after initial and multiple sessions (50% vs. 61%; P = .386, 73% vs. 79%; P = .530), however, differences were observed in the PVI alone group (27% vs. 61%; P = .018, 49% vs. 78%; P = .046). Conclusions: The presence of LVAs was associated with an arrhythmogenic SVC. An SVCI may have the potential to compensate for an impaired outcome after a PVI in non‐PAF patients with LVAs. Abstract : The LVAs was associated with an arrhythmogenic SVC in non‐PAF patients. An SVCI compensated for an impaired outcome after PVI in non‐PAF patients with LVAs.